Pelatihan Literasi Keuangan Digital Untuk Meningkatkan Kemampuan Pengelolaan Keuangan Masyarakat Di Desa Bangbayang Kecamatan Lemahsugih Kabupaten Majalengka - Asep Saeful Falah (Jurnal Pengabdian Kepada Masyarakat Multi Disiplin, 2026)
The development of information technology has driven the transformation of financial services toward digital systems that are faster, easier, and more efficient. However, the level of digital financial literacy among rural communities remains relatively low, highlighting the need for continuous educational efforts. This community service program aims to improve the understanding and skills of the residents of Bangbayang Village, Lemahsugih District, Majalengka Regency, in utilizing digital financial services safely and productively. The methods employed included counseling sessions, demonstrations, hands-on practice, discussions, and evaluations through pre-tests and post-tests. The results of the program indicated an improvement in participants' understanding of mobile banking, digital wallets, QRIS, household financial management, and digital transaction security.